Alterations of Brain Structural Network Connectivity in Type 2 Diabetes Mellitus Patients With Mild Cognitive Impairment - Li, Chang; Zhang, Jingna; Qiu, Mingguo; Liu, Kaijun; Li, Yang; Zuo, Zhiwei; Yin, Xuntao; Lai, Yuqi; Fang, Jingqin; Tong, Haipeng; Guo, Yu; Wang, Jian; et al. (Frontiers in Aging Neuroscience, 2021)
Patients with Type 2 diabetes mellitus (T2DM) are highly susceptible to developing dementia, especially for those with mild cognitive impairment (MCI), but its underlying cause is still unclear. This study aims to investigate early detection of white matter structural network changes in T2DM patients with MCI and assess the relationship between cognitive impairment and structural network alterations in T2DM patients. In this study, we performed a battery of neuropsychological tests and diffusion tensor MRI in 30 T2MD-MCI patients, 30 T2DM patients with normal cognition (T2DM-NC) and 30 age-, sex-, and education-matched healthy control (HC) individuals. Cognitive performance exhibited obvious difference among three groups. The structural network was significantly disrupted in both global and regional levels in T2DM patients. T2DM-MCI group showed more severe impairment of global network efficiency, and lower nodal efficiency and less connections within multiple regions like limbic system, basal ganglia and several cortical structures. Moreover, a subnetwork impaired in T2DM-MCI was characterized by cortical-limbic fibers, commissural fibers and pathways within frontal, temporal and occipital lobes. These altered global and nodal parameters were significantly correlated with cognitive function in T2DM-MCI patients. In particular, the executive dysfunction and working memory impairment in T2DM-MCI patients correlated with nodal efficiency in the right opercular part and triangular part of inferior frontal gyrus, which indicates white matter disruption in these regions may act as potential biomarkers for T2DM associated MCI detection. Our investigation provides novel insight into the neuropathological effects of white matter network disruption on cognition impairments induced by T2DM.